Industry-level emission trading between power producers in the EU - Christoph Böhringer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
In this paper we investigate how restrictions for emission trading to the energy-intensive power sector will affect the magnitude and distribution of abatement costs across EU countries vis-?-vis a comprehensive EU emission trading regime. We find that emission trading between European power sectors allows the harvest of a major part of the efficiency gains provided by full trade as compared to strictly domestic action. However, trade restrictions may create a more unequal distribution of abatement costs across member states than is the case for a comprehensive trade regime. The reason for this is that restricted permit trade enhances the secondary terms-of-trade benefits to EU member countries with low marginal abatement costs at the expense of the other EU member states.
Keywords: D58; Q43; Q58; 330; emission trading; computable general equilibrium; Umweltverträgliche Energiepolitik; Energiewirtschaft; Luftverunreinigung; Emissionsrechte; Außenhandelsbeschränkung; Allokationseffizienz; Wohlfahrtseffekt; Allgemeines Gleichgewicht; EU-Staaten